Excessive ethanol consumption under exposure to lead intensifies disorders in bone metabolism: A study in a rat model - Kupraszewicz, Elżbieta; Brzóska, Malgorzata M. (Chemico-biological interactions, 2013)
► Exposure to lead (Pb) or/and ethanol (Et) disturbs bone metabolism in male rats. ► Et abuse under exposure to Pb increases the risk of bone damage. ► Excessive Et consumption decreases Pb accumulation in the skeleton. ► Destroying of the RANK/RANKL/OPG system is involved in interactive action of Pb and Et on bone. It was investigated whether ethanol (Et) modifies the damaging impact of lead (Pb) on bone metabolism in a rat model reflecting excessive alcohol consumption by humans exposed to relatively high levels of this metal. For this purpose, markers of bone formation (osteocalcin, procollagen I, osteoprotegerin, alkaline phosphatase) and resorption (telopeptides of collagen I, soluble receptor activator of nuclear factor-κB ligand), calciotropic hormones (parathormone, calcitonin, 25-hydroxyvitamin D and 1,25-dihydroxyvitamin D) in the serum, and the femur content of mineral (including calcium – Ca and inorganic phosphorus – Pi) and organic components were estimated in the rats exposed to 500mg Pb/l (in drinking water) or/and Et (5g/kg b.wt./24h, by oral gavage) for 12weeks. Moreover, Ca and Pi in the serum and urine, alkaline phosphatase in the bone tissue and Pb in the blood and femur were determined. The exposure to Pb or/and Et decreased bone formation and increased its resorption resulting in the bone demineralization. These effects were accompanied by destroying the hormonal regulation of mineral metabolism, and Ca and Pi imbalance. The co-exposure to Pb and Et-induced disorders in bone metabolism were more advanced than those caused by Pb alone. Et co-administration increased Pb concentration in the blood and decreased its accumulation in the bone. This paper is the first report providing evidence that consumption of Et under exposure to Pb intensifies disorders in bone metabolism and that destroying of the receptor activator nuclear factor-κB (RANK)/RANK ligand/osteoprotegerin system is involved in the mechanisms of interactive action of these xenobiotics on the skeleton. The modifying impact of Et may be an effect of its independent osteotropic action and interaction with Pb. Based on the results it can be concluded that alcohol abuse by subjects excessively exposed to Pb considerably increases the risk of bone damage.